Bullying among undergraduate medical students at Tanta University, Egypt: a cross-sectional study. Issue 1 (1st January 2020) - Elghazally, Noha Mohammed; Atallah, Asmaa Omar
ABSTRACT: Introduction: Bullying is an aggressive behaviour that involves unwanted negative actions, which are repeated over time that can negatively impact a person. Aim: To explore bullying behaviours experienced by Tanta University undergraduate students during their study in clinical medical education. Methods: A cross-sectional study was conducted at Faculty of Medicine, during the period between first of October 2018 to end of May 2019. A stratified random sample was used to select medical students who rolled fourth-, fifth- and sixth-year classes at the academic year 2018–2019. Data were collected by a self-administered questionnaire included questions regarding demographic characteristics, history of exposure to different types of bullying and the response of bullied students. Results: Findings of this study revealed that 71.1% of studied sample faced bullying during their medical study. The most frequently reported types were verbal (51.9%), behavioural (44.8%), being ignored (24.4%), written (17.8%) and physical (15.8%). About half of students (49.4%) were exposed to multiple forms of bullying. Male students were more exposed to physical, written and being ignored, whereas females were more witnessed to verbal and behavioural ones as follows: (30.7% vs 18.9% physical type, 72.5% vs 74.8% verbal, 28.1 vs 24.9% written, 57.9% vs 68.3% behavioural and 38.5% vs 32.4% being ignored), respectively. Fellow students (56.3%) were the most frequent perpetrators of mistreatment actions. The majority of students (91.3%) chose not to report bullying behaviours. Having mental health problems (0.00*) or disability (0.01*) were significantly more potential to experience mistreatment. Discussion: Large proportion of medical students faced many forms of bullying. Implications for Practice: Applying an effective policy to stop bullying with support for medical students may help to minimize this phenomenon.